Valorization of Brewer’s Spent Grain Using Biological Treatments and its Application in Feeds for European Seabass (Dicentrarchus labrax) - Fernandes, Helena; Salgado, José Manuel; Ferreira, Marta; Vršanská, Martina; Fernandes, Nélson; Castro, Carolina; Oliva-Teles, Aires; Peres, Helena; Belo, Isabel (Frontiers in Bioengineering and Biotechnology, 2022)
Brewer’s spent grain (BSG) is the main brewery by-product, with applications in the feed and food industries. Also, the lignocellulosic nature of BSG makes it an adequate substrate for carbohydrases production. In this work, solid-state fermentation (SSF) of BSG was performed with Aspergillus ibericus, a non-mycotoxins producer fungus with a high capacity to hydrolyze the lignocellulosic matrix of agro-industrial by-products. SSF was performed at different scales to produce a crude extract rich in cellulase and xylanase. The potential of crude extract was tested in two applications: 1-the enzymatic hydrolysis of fermented BSG and 2-as supplement in aquafeeds. SSF of BSG increased protein content from 25% to 29% (w/w), while fibre was reduced to 43%, and cellulose and hemicellulose were markedly reduced to around 15%. The scale-up of SSF from 10 g of dry BSG in flasks to 50 g or 400 g in tray-type bioreactors increased 55% and 25% the cellulase and xylanase production, up to 323 and 1073 U g-1 BSG, respectively. The optimum temperature and pH of maximal activities were found to be 55 °C and pH 4.4 for xylanase, and 50 °C and pH 3.9 for cellulase, being cellulase more thermostable than xylanase at temperatures from 45 °C to 60 °C. A Box-Behnken factorial design was applied to optimize the hydrolysis of fermented BSG by the crude extract. Crude extract load was significant in sugars release, highlighting the role of hydrolytic enzymes, while substrate load, fermented BSG, and the addition of commercial β‐glucosidase were responsible for the highest phenolic compounds and antioxidant activity release. The lyophilized crude extract (12400 and 1050 U g-1 lyophilized extract, xylanase, and cellulase, respectively) was also tested as an enzyme supplement in aquafeed for European seabass (Dicentrarchus labrax) juveniles. The dietary supplementation with the crude extract improved feed and protein utilization. Processing of BSG using biological treatments, as SSF with A. ibericus, produced a nutritionally enriched BSG and a crude extract with highly efficient carbohydrases capable of hydrolysing lignocellulosic substrates, such as BSG, and with the potential to be used as feed enzymes improving feed utilization of an important aquaculture fish species.